1999
DOI: 10.1046/j.1365-313x.1999.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

KCS1encodes a fatty acid elongase 3‐ketoacyl‐CoA synthase affecting wax biosynthesis inArabidopsis thaliana

Abstract: SummaryAn Arabidopsis fatty acid elongase gene, KCS1, with a high degree of sequence identity to FAE1, encodes a 3-ketoacyl-CoA synthase which is involved in very long chain fatty acid synthesis in vegetative tissues, and which also plays a role in wax biosynthesis. Sequence analysis of KCS1 predicted that this synthase was anchored to a membrane by two adjacent N-terminal, membrane-spanning domains. Analysis of a T-DNA tagged kcs1-1 mutant demonstrated the involvement of the KCS1 in wax biosynthesis. Phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
292
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(302 citation statements)
references
References 44 publications
9
292
0
1
Order By: Relevance
“…Phaseolus vulgaris (Steinmüller and Tevini, 1985), Medicago truncatula (Zhang et al, 2005), and Pisum sativum (Gniwotta et al, 2005; the composition of V. faba leaf wax has not been reported yet). Arabidopsis flower wax is dominated by C 29 alkane (Shi et al, 2011), shorter than the prevalent C 31 homolog in leaves (Jenks et al, 1995) but similar to inflorescence stems and siliques (Todd et al, 1999). Overall, there appears to be a fairly widespread compositional pattern in flower waxes, in many species characterized by the presence of shorter chain lengths than on vegetative organs.…”
Section: Discussionmentioning
confidence: 95%
“…Phaseolus vulgaris (Steinmüller and Tevini, 1985), Medicago truncatula (Zhang et al, 2005), and Pisum sativum (Gniwotta et al, 2005; the composition of V. faba leaf wax has not been reported yet). Arabidopsis flower wax is dominated by C 29 alkane (Shi et al, 2011), shorter than the prevalent C 31 homolog in leaves (Jenks et al, 1995) but similar to inflorescence stems and siliques (Todd et al, 1999). Overall, there appears to be a fairly widespread compositional pattern in flower waxes, in many species characterized by the presence of shorter chain lengths than on vegetative organs.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, as shown below, the first 46 N-terminal residues are not essential for enzymatic activity. Another difference noted is that only four of the six Cys residues conserved in other Kcs proteins (Todd et al, 1999) are present in the algal Kcs. Recently reported mutagenesis experiments indicated that only a single Cys residue (residue 223 in the Arabidopsis FAE1) was essential for activity (Ghanevati and Jaworski, 2001).…”
Section: Cloning Of a Salt-inducible Kcs From D Salinamentioning
confidence: 96%
“…Additional plant genes belonging to this family were identified on the basis of sequence homology or as transposon insertion sites in tagged mutants (Fourman et al, 1998;Millar et al, 1998;Yephremov et al, 1999;Priutt et al, 2000). Functionally characterized plant kcs genes include genes expressed in seeds and active in the biosynthesis of storage lipids or waxes (Lassner et al, 1996), as well as genes expressed in vegetative tissues and involved in the biosynthesis of cuticular waxes (Millar et al, 1999;Todd et al, 1999). The D. salina Kcs, identified in the context of algal salt responses, is most likely involved in membrane lipid biosynthesis.…”
mentioning
confidence: 99%
“…During this process, the C16 and C18 fatty acids synthesized in the plastids are exported to the cytosol, where they are further elongated to VLCFAs in the range of 20 to 34 carbons by the fatty acid elongase complex on the endoplasmic reticulum (ER; Millar and Kunst, 1997;Millar et al, 1999;Todd et al, 1999;Yephremov et al, 1999;Fiebig et al, 2000;Clemens and Kunst, 2001;Hooker et al, 2002;Dietrich et al, 2005;Zheng et al, 2005). The elongated VLCFAs are then further transformed by two principal wax biosynthetic pathways: an acyl reduction pathway that produces primary alcohols and wax esters, and a decarbonylation pathway that leads to the formation of aldehydes, alkanes, secondary alcohols, and ketones (Aarts et al, 1995;Kunst and Samuels, 2003;Rowland et al, 2006).…”
mentioning
confidence: 99%